Penerapan Sosial Media dan Brand Image terhadap Pemasaran Produk Bank Syariah - Erika Amalia; Hadilla Maryati; Lidia Desiana (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
As technology rapidly advances, the internet and social media have become an integral part of everyday life. Social media, which has evolved significantly since the Web 2.0 and 3.0 eras, plays a crucial role in communication and marketing. In this context, Bank Syariah Indonesia utilizes social media as a marketing tool to reach customers, particularly the millennial generation, who are highly reliant on digital technology. This study aims to explore the application of social media in the marketing of Islamic bank products and how brand image influences customer decisions. The use of social media platforms such as Instagram, Facebook, Twitter, and TikTok allows the Islamic bank to introduce products and expand its market reach more efficiently. Furthermore, the research indicates that marketing through social media significantly influences consumer purchase intent and strengthens brand image. The bank's brand image is also influenced by product quality, responsive customer service, and the company's reputation, all of which contribute to increased customer trust. With the right digital marketing strategy, the Islamic bank can enhance operational efficiency, strengthen its market position, and provide better services to customers.